Analysis of genetic divergence in fenugreek (Trigonella foenum-graecum L.) - Kole, Ananya Banerjee, P C (Journal of Spices and Aromatic Crops, 2004)
Genetic divergence among 22 genotypes of fenugreek (Trigon ella foenum-graecum) was estimated for 8 quantitative characters using Mahalanobis's D' statistic and the genotypes were grouped into 6 clusters. Cluster I consisted of maximum number of 13 genotypes followed by 4 and 2 genotypes in clusters II and III, respectively. Three clusters were monogenotypic. Clustering pattern of genotypes was not related to geographical differentiation. Inter-cluster distance was highest between clusters III and VI and lowest between clusters II and VI while, intra-cluster distance was highest in cluster III. Plant height, pods plant-1, days to flowering and test weight were the major forces for divergence.